War games for civilians: application experiences in a master’s program - Gática Bórquez, Jorge.; Harvey Valdés, Hugo Enrique. (Escuela Militar de Cadetes, 2023)
This article aims to expose the experiences obtained in the application of an exercise under the modality of war games in the Master in Strategic Intelligence of the National Academy of Political and Strategic Studies of Chile. This methodology was used to practice and train the theoretical contents, using all the students, civil and military, from various disciplines. The main findings refer to individual and group attitudes and capacities, as well as analytical and decision-making processes. Additionally, lessons were obtained for the program, the game itself, and the professional performance of the function. Finally, evidence is exposed that this type of exercise allows one to achieve significant experiences in conditions similar to real ones and is relevant to complete an educational process in programs of this nature.
Keywords: Inteligencia estratégica; Juego de guerra; Simulación; Toma de decisiones